Enhancing e-government in digital transformation: integrating archive management and digital solutions in Pekanbaru, Indonesia - Rahman, Khairul; Adni, Dita Fisdian; Nasution, M Ari Tri Putra (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
Efficient and modern archive management is very important in this digital era, especially at the local government level. In this context, this study explores the urgency of archive management using the Integrated Dynamic Archival Information System (SRIKANDI) approach in the Pekanbaru City Government. The research method used is qualitative, with data sources from interviews, documentation, and observation and analysis using the NVivo 12 Plus software. The study's results identified challenges to SRIKANDI implementation, including inadequate technological infrastructure, the need for skilled human resources in information technology, attention to data security, changes in organizational culture, and ongoing technical support. Based on these findings, policy recommendations have been made, including investments in technology infrastructure, human resource training and development, strict data protection, and changes in organizational culture. This research has positive implications for archive management, increasing efficiency and accountability in Pekanbaru. This research provides insights for other city governments wishing to undertake similar digital transformations in electronic-based archives management